Analisis Laporan Keuangan Dalam Menilai Kinerja Keuangan PT Satria Antaran Prima Tbk Periode 2021-2024 - Sirait, Jersi Riani Br; Riny Jefri (PT. Karya Inovatif Nusantara, 2025)
This study investigates the financial statement analysis undertaken to evaluate the financial performance of PT Satria Antaran Prima Tbk. The research employs quantitative descriptive approach utilizing three categories including liquidity, solvency, and profibality ratios. The financial statement data used in this study are secondary data for the period 2021-2024 obtained from the Indonesia Stock Exchange. The results reveal that the company’s overall financial condition is relatively poor. From the liquidity perspective, the company’s financial condition is considered favorable from the creditors’ standpoint, as the liquidity remains within the safe threshold, however it is less favorable from the investors’ perspective since the decrease in liquidity does not contribute to grow investment value to generate higher profits. In terms of solvency and profitability, the company’s performance is also considered poor, as the solvency ratios tends to increase while the profitability ratio tends to decrease. Although the profitability ratio has declined, the company possesses a big substantial other comprehensive income (OCI) particularly in 2024. This component is not included in the ratio since the profit used in the analysis represents net income after tax. However, according to previous study, the value of OCI can be considered an indicator for forecasting future cash flows.